Sistem Pendukung Keputusan Seleksi Pemberian Bantuan Langsung Tunai pada Masyarakat Mareda Wuni Berbasis Web Menggunakan PROMETHEE - Bernardino Stefen Goro; Andreas Ariyanto Rangga; Felysitas Ema O Sanga (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Village development includes village funding, and the community takes the lead in developing and initiatives that advance village welfare are developed through cooperation with the community. Village development is an important instrument that must be used because it directly improves the welfare of the village community. Village communities are the focus of development, and each village is given the authority by the government to carry out its own development according to its capacity. Thus, the government supports the improvement of village development and empowerment. Village funds are used to provide or improve village public services, reduce poverty, advance the village economy, and reduce tandem between villages. This study uses a weighted summation approach of alternative rankings on all attributes, which is often known as the Simple Additive Weighting method. To determine which residents receive social assistance, the system can calculate the value of the multi-criterion preference index, preference value, outflow, inflow, and net flow for each alternative and sub-criterion.